Adsorption Of Uranium From Carbonate Media - J. H. Canterford (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1985)
The adsorption of uranium onto Wyoming bentonite was measured in carbonate media over the pH range 8 to 11. Uranium was removed from solution onto the solids by a rapid reaction, proposed to be adsorption of the anionic uranyl tricarbonato complex onto edges of the clay platelets, and a slow reaction that may be precipitation of a hydroxide. The changes in uranium content of the aqueous and solid phases of a uranium ore carbonate leach slurry were also measured as the slurry was progressively diluted. There was an increase in the uranium content of the solids as the pH of the suspension was lowered, as observed with the Wyoming bentonite. Results indicate the conditions that should be met with respect to pH control to prevent the problem of excessive uranium adsorption in the counter-current decantation washing circuit of a conventional leaching process, as well as in the leaching and restoration phases of carbonate solution mining.